QoS-aware ant-based route, wavelength and timeslot assignment algorithm for optical burst switchednetworks - Coulibaly, Yahaya (Wiley-Blackwell, 2015)
All-optical networks are the aspiration of bandwidth-greedy applications providers and users such as telecom operators and scientific research centres. Because of the limitations of current network infrastructures, some optical switching paradigms have been proposed. Among these paradigms, optical burst switching (OBS) is seen as the most appropriate solution. However, OBS suffers from high burst loss ratio as a result of contention at the buffer-less core node. According to current optical technology reviews, cost effective optical memories are yet to be cost effective. In this paper, an ant-based route, wavelength and timeslot allocation algorithm is proposed to address high burst loss in OBS and improve the overall network performance. The solution was implemented in hierarchical time-sliced OBS and was evaluated through computer simulation where it was compared with shortest path (SP) algorithm. Simulation results show that the proposed algorithm outperforms SP in terms of burst loss ratio and delay.